TANTANGAN DAN STRATEGI GURU DALAM MENGHADAPI TRANSFORMASI DIGITAL DI SEKOLAH BERBASIS PONDOK PESANTREN - Nuha, Muhammad Ullin; Mutaharoh, Lilik; Sherley Juristi Hidayat (Al Irfan : Jurnal Ilmu Pendidikan dan Penelitian, 2026)
Digital transformation has significantly changed the educational paradigm, including within formal schools based in pesantren. This study aims to analyze the challenges faced by teachers and identify strategies for dealing with digital transformation in the pesantren environment. This research uses a qualitative approach with a library research method, analyzing various scientific literatures and relevant theoretical studies. The results indicate that the main challenges for teachers include limited digital literacy, a lack of structured training, infrastructure constraints, and resistance to change due to concerns about the degradation of traditional values. Strategies identified to overcome these challenges involve increasing teacher competence through the TPACK  framework, implementing blended learning models, and integrating Islamic values into technology use. This study concludes that successful digital transformation in pesantren-based schools depends on the teacher's ability to balance technological innovation with the preservation of the pesantren's traditional characteristics and moral values.